ANALISIS KEGIATAN MBKM-KEWIRAUSAHAAN: CULINARY CORONET - Tunjungsari, Hetty Karunia; Demetrius, Felix; Hartojo, Graciella Jocelyn; Leviani, Marissa; Alvindy (Jurnal Serina Abdimas, 2024)
This study analyzes the impact of the MBKM-Entrepreneurship Program on the development of the Culinary Coronet (CuCo) business, a pastry venture founded by four Management students from Tarumanagara University. CuCo, with its flagship product named Culinary Coronet, is committed to becoming a leading pastry producer in Indonesia through innovation and high quality. This research uses a qualitative descriptive method with a case study approach, collecting data through observation, interviews, and document analysis. During the period from April to September 2024, CuCo increased production quantity from 250 to 500 units per month and revenue from Rp4,500,000 to Rp9,000,000 per month. Financial reports show an increase in gross profit and a positive net cash flow. The results of the study indicate that the MBKM-Entrepreneurship Program had a significant positive impact on CuCo's development, enabling the team to develop innovative products, expand marketing networks, and improve operational efficiency through training and guidance. Support from supervising lecturers and university facilities also played an important role in this success. The conclusion of this study is that the MBKM-Entrepreneurship Program effectively promotes student business development, particularly in the pastry industry in Indonesia. This program successfully enhanced the capacity and capability of the CuCo team, contributing to sustainable business growth. This research is expected to serve as a reference for the development of similar programs in the future and provide inspiration for other students to develop their own ventures. ABSTRAK Penelitian ini menganalisis pengaruh Program MBKM-Kewirausahaan terhadap pengembangan bisnis Culinary Coronet (CuCo), sebuah usaha pastry yang didirikan oleh empat mahasiswa Manajemen dari Universitas Tarumanagara. CuCo, dengan produk unggulan bernama Culinary Coronet, berkomitmen menjadi produsen pastry terkemuka di Indonesia melalui inovasi dan kualitas tinggi. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan studi kasus, mengumpulkan data melalui observasi, wawancara, dan analisis dokumen terkait. Selama periode April hingga September 2024, CuCo meningkatkan kuantitas produksi dari 250 menjadi 500 unit per bulan dan pendapatan dari Rp4.500.000 menjadi Rp9.000.000 per bulan. Laporan keuangan menunjukkan peningkatan laba kotor dan arus kas bersih yang positif. Hasil penelitian menunjukkan bahwa Program MBKM-Kewirausahaan memberikan dampak positif signifikan terhadap pengembangan CuCo, memungkinkan tim mengembangkan produk inovatif, memperluas jaringan pemasaran, serta meningkatkan efisiensi operasional melalui pelatihan dan bimbingan. Dukungan dari dosen pembimbing dan fasilitas universitas juga berperan penting dalam keberhasilan ini. Kesimpulan penelitian ini adalah bahwa Program MBKM-Kewirausahaan efektif mendorong pengembangan bisnis mahasiswa, khususnya dalam industri pastry di Indonesia. Program ini berhasil meningkatkan kapasitas dan kapabilitas tim CuCo, berkontribusi pada pertumbuhan bisnis yang berkelanjutan. Penelitian ini diharapkan menjadi referensi bagi pengembangan program serupa di masa mendatang dan memberikan inspirasi bagi mahasiswa lain untuk mengembangkan usaha mereka.